Effects of specific muscle imbalance improvement training on the balance ability in elite fencers - Kim, T.; Kil, S.; Chung, J.; Moon, J.; Oh, E. (Journal of Physical Therapy Science, 2015)
[Purpose] The lunge Motion that occurs frequently in fencing training and matches results in imbalance of the upper and lower limbs muscles. This research focuses on the improvement of the imbalance that occurs in the national team fencers of the Republic of Korea through specific muscle imbalance improvement training. [Subjects] The subjects of this research were limited to right-handed male fencers. Nine male, right-handed national fencing athletes were selected for this study (4 epee, 5 sabre; age 28.2 ± 2.2 years; height 182.3 ± 4.0 cm; weight 76.5 ± 8.2 kg; experience 12.4 ± 3.0 years). [Methods] The specific muscle imbalance improvement training program was performed for 12 weeks and Pre-Post tests were to evaluate its effect on the experimental group. Measurements comprised anthropometry, test of balance, and movement analysis. [Results] After the training program, mediolateral sway of the nondominant lower limb and the balance scale showed statistically significant improvement. [Conclusion] The specific muscle imbalance improvement training program used in this research was proven to be effective for improving the muscle imbalance of elite fencers.